2016
DOI: 10.1021/acs.est.6b03734
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, Translocation, and Metabolism of 8:2 Fluorotelomer Alcohol in Soybean (Glycine max L. Merrill)

Abstract: Biotransformation of fluorotelomer alcohols (FTOHs) is widely considered as an additional source of perfluorocarboxylic acids (PFCAs) in environmental biota. Compared with the extensive studies conducted in animals and microbes, biotransformation pathways of FTOHs in plants are still unclear. In this study, a hydroponic experiment was conducted to investigate the uptake, translocation and metabolism of 8:2 FTOH in soybean (Glycine max L. Merrill) over 144 h. 8:2 FTOH and its metabolites were found in all parts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 52 publications
0
46
0
3
Order By: Relevance
“…Moreover, conjugation with xenobiotics by GSH may be a common pathway for plant metabolism of various man-made chemicals (Neuefeind et al, 1996). Glutathione conjugation with diclofenac (Bartha et al, 2014), 8:2 fluorotelomer alcohol (Zhang et al, 2016) and chlortetracycline (Farkas et al, 2007) have been previously observed in plants. It is well known that these processes require extensive utilization of reduced GSH as an electron donor and subsequently produce oxidized glutathione (GSSG).…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, conjugation with xenobiotics by GSH may be a common pathway for plant metabolism of various man-made chemicals (Neuefeind et al, 1996). Glutathione conjugation with diclofenac (Bartha et al, 2014), 8:2 fluorotelomer alcohol (Zhang et al, 2016) and chlortetracycline (Farkas et al, 2007) have been previously observed in plants. It is well known that these processes require extensive utilization of reduced GSH as an electron donor and subsequently produce oxidized glutathione (GSSG).…”
Section: Discussionmentioning
confidence: 87%
“…明显降低, 间接证明了CYP450酶在CB-3转化过程中 的作用 [33] . 大豆能将8:2氟调醇代谢转化为8:2氟调醛 和8:2氟调羧酸, 通过检测大豆体内涉及I相转化的几 种酶的活性, 发现大豆根部ADH和ALDH的酶活性显 著增加 [34] , 侧面证明了ADH与ALDH在8:2氟调醇I相 转化过程中的作用. 还原脱卤作用是卤代有机污染物 生物转化过程中常见也非常重要的I相反应, NaR等酶 在这个过程中起到重要作用.…”
Section: I相反应过程涉及的酶主要有细胞色素p450酶unclassified
“…体内发生脱溴过程, 生成五溴环十二烷(PBCD)和四溴 环十二烷(TBCD) [43] . 链状的卤代烷烃, 如8:2氟调醇在 大豆体内发生脱氟反应, 生成8:2不饱和氟调酸、全氟 辛烷羧酸以及7:3氟调羧酸 [34] . 短链氯化石蜡单体化合 物1,2,5,5,6,9,10-heptachlorodecane (1,2,5,5,6,9,10-HepCD)在南瓜幼苗体内发生转化, 有4%发生了氯重 排, 42%发生了脱氯反应 [58] .…”
Section: 对于非苯环类环状溴代污染物Hbcd 同样会在植物unclassified
See 1 more Smart Citation
“…However, the intact plant experiments conducted in hydroponic solution or soil are usually labor-intensive and time-consuming. The presence of microorganisms and root exudates also influence pharmaceutical metabolism, which cannot be excluded from the in vivo studies (Yu et al, 2013;Zhang et al, 2016). The uptake and transport processes could further complicate the metabolism of pharmaceuticals in plants by governing the input and output of parent compounds/metabolites in a specific plant part.…”
Section: Introductionmentioning
confidence: 99%